Potential effects of lowering the BAC limit on injuries, fatalities, and costs - Kostyniuk, L.; Eby, D.; Molnar, L.; St Louis, R.; Zanier, N.; Miller, Ted (Pergamon, 2018)
© 2017 Elsevier Ltd and National Safety Council Introduction: Potential health and cost impacts of lowering the BAC limit for U.S. drivers below.08% were explored through analyses of reductions in crash incidence, injury severity, and costs based on five scenarios with varying assumptions about how the change to a.05% BAC limit might affect alcohol-impaired driving. Methods: Distribution of crashes by injury level and highest driver or non-occupant BAC levels for 2010, together with unit crash costs provided a base for comparison. Scenario 1 assumed all alcohol-impaired driving ceased; scenario 2 assumed all drivers obeyed the law, and scenario 3 assumed decreases in driver BAC levels would be limited to those who had been driving near the legal limit before the change. Scenario 4 was based on changes in driver BAC levels associated with a 08% to.05% BAC limit change in Australia, and scenario 5 was based on changes in alcohol-related crashes associated with the change to the.08% BAC limit in the United States. The number of casualties prevented in each scenario was estimated using relative risks of crash involvement, and changes in societal costs were estimated using the unit costs. Results: Reductions ranging from 71% to 99% in fatalities, injuries, and costs related to alcohol-impaired driving were estimated in scenarios 1 and 2. Scenarios 3–5 produced smaller reductions ranging from 4% to 16% for alcohol-impaired fatalities, injuries, and costs. Conclusion: The wide difference between the outcomes of the two sets of scenarios reflects the sensitivity of BAC policy benefits to driver compliance behavior. Practical application: The quantification of the reduction in the number and costs of traffic crash casualties in the set of behavioral scenarios explored in this research can inform policymakers about the extent and limits of benefits achievable by lowering the BAC limits as they consider strategies to reduce alcohol-impaired driving.